Free radical scavenging and antimicrobial properties of extracts of wild mushrooms - Oyetayo,V.O. (2009)
Antioxidant and antimicrobial potentials of extracts obtained from four wild mushrooms, Termitomyces clypeatus (TCE), Termitomyces robustus (TRE), Lentinus subnudus (LSE) and Lenzites species (LZE) collected in Nigeria were investigated. LSE and LZE displayed good scavenging activity against 2, 2-Diphenyl-1-Picrylhydrazyl (DPPH) and ferrous ion radicals at concentration of 2 mg/mL. However, TRE and TCE exhibited better superoxide anion scavenging effect at 2 mg/mL. All extracts (TCE, TRE, LSE and LZE) had comparable scavenging effect on hydroxyl radicals as butylated Hydroxytoluene (BHT) used as control. Moreover, extracts from the wild mushrooms were able to inhibit the growth of all indicator organisms at concentrations between 12.5 mg/mL to 100 mg/mL. LSE and LZE, however, showed better antimicrobial effect on the indicator organisms. The results suggest that extracts obtained from the four wild mushrooms may serve as sources of new bioactive compounds with effective antioxidant and antimicrobial activity.